Borrowed institutions and African exceptionalism: a critique (2010)
This paper critiques the view that attributes the crisis of the state and governance in Africa to the contradiction between African values and indigenous processes of governance, and borrowed institutions. It argues that engaging political institutions in a detailed comparative manner shows how and why similar institutions borrowed from the West have worked in some developing countries and have been less than successful in others. An engagement with institutional theory from the perspective of Africa should aim to bring African experience to bear on issues rather than merely to show how unworkable they are in Africa.